MOTHERS’ ACTIVE CONTRIBUTION AGAINST YOUNG GENERATIONS IN PREVENTING THE SPREAD OF COVID-19 PANDEMIC - I Gusti Bagus Hengki; Made Emy Andayani Citra; I Gusti Ngurah Anom; I Made Kariyasa (Unmas Press, 2021)
The active contribution of a mother/woman in activities to prevent the spread of the Covid-19 pandemic is very necessary because mothers have a natural role as the primary and first educators for children from the time the fetus is in the womb to growing and developing into the younger generation. To carry out the prevention of Covid-19 persuasively and educationally, it is necessary to have two-way communication between mothers and children, between mothers and husbands, between mothers and other family members. Besides communication through the family line, communication is also carried out through the school and community channels. Groups of women/mothers based on different professions, cultures, customs, languages ​​, and ancestral (ethnic) ties also have a role in preventing the spread of the Covid-19 pandemic to all generations of the nation. The program carried out is to socialize health protocols: wear masks, wash hands, cover mouth when sneezing and coughing, social distancing and adequate rest and nutritious eating. The juridical foundation for mothers/women to actively contribute to the younger generation in preventing the spread of the Covid-19 pandemic is based on the ideological foundation of the Republic of Indonesia, namely Pancasila and the 1945 Constitution of the Republic of Indonesia and Human Rights and laws and regulations relating to legal protection and equality of gender roles in state life. This study used a normative legal research methodology with an applied normative. The data were analyzed qualitatively on the natural roles of mothers/women in the family, the gender roles of mothers/women in school, and the gender roles of mothers/women in society. This study found that mothers/women have a natural role to actively participate in preventing the spread of Covid-19.